Management of Common Resources and Reciprocity:: the contributions of Elinor Ostrom to the Debate - Sabourin, Eric (Sustainability in Debate, 2010)
This paper analyzes the importance of reciprocity in the processes and procedures recorded in the management of common resources. It examines first the role that E. Ostrom attributes to the norm of reciprocity in her approach to common property resources. A second part interprets economic and social relations in the management of common resources as seen by economic anthropology’s theory of reciprocity. Finally, the conclusion attempts to establish a dialogue between Ostrom’s proposals and the theory of reciprocity.